Laparoscopic surgery for duodenal perforation due to a diverticulum with heterotopic pancreas: a case report - Shu Tsukihara; Shinji Onda; Kyonsu Son; Daisuke Ito; Hironori Kanno; Toshiaki Morikawa; Nobuyoshi Hanyu; Ken Eto (Surgical Case Reports, 2022)
Abstract Background Heterotopic pancreas (HP) refers to the presence of abnormally located pancreatic tissue without any anatomic or vascular continuity with the main body of the pancreas. HP can occur in the gastrointestinal tract and be complicated by gastrointestinal bleeding, pancreatitis, obstruction, or malignant generation. Specifically, perforation of the gastrointestinal tract because of HP is extremely rare. Case presentation A 91-year-old woman was diagnosed with duodenal perforation, and an emergency laparoscopic operation was performed. The operative findings indicated a tumor and duodenal wall perforation. The tumor and the perforated site were resected with a linear stapler. Histopathological examination revealed the presence of HP tissue in the submucosal layer around the diverticulum without any signs of inflammation. The perforated site was not covered by HP tissues, and the duodenal wall might have been weaker than the other areas, which could have caused the internal pressure to increase and led to the perforation. Conclusions Preoperative HP diagnosis is difficult, and it is crucial to consider HP as the differential diagnosis in gastrointestinal perforations. The duodenal diverticula can be perforated due to increased internal pressure of the duodenum caused by the imbalanced localization of HP.